Crimp length decreases in lax tendons due to cytoskeletal tension, but is restored with tensional homeostasis. Issue 3 (14th December 2016) - Lavagnino, Michael; Brooks, Andrew E.; Oslapas, Anna N.; Gardner, Keri L.; Arnoczky, Steven P.
ABSTRACT: Collagen crimp morphology is thought to contribute to the material behavior of tendons and may reflect the local mechanobiological environment of tendon cells. Following loss of collagen tension in tendons, tenocytes initiate a contraction response that shortens tendon length which, in turn, may alter crimp patterns. We hypothesized that changes in the crimp pattern of tendons are the result of cell‐based contractions which are governed by relative tautness/laxity of the collagen matrix. To determine the relationship between crimp pattern and tensional homeostasis, rat tail tendon fascicles (RTTfs) were either allowed to freely contract or placed in clamps with 10% laxity for 7 days. The freely contracting RTTfs showed a significant decrease in percent crimp length on both day 5 (3.66%) and day 7 (7.70%). This decrease in crimp length significantly correlated with the decrease in freely contracting RTTf length. Clamped RTTfs demonstrated a significant decrease in percent crimp length on day 5 (1.7%), but no significant difference in percent crimp length on day 7 (0.57%). The results demonstrate that the tendon crimp pattern appears to be under cellular control and is a reflection of the local mechanobiological environment of the extracellular matrix. The ability of tenocytes to actively alter the crimp pattern of collagen fibers also suggests that tenocytes can influence the viscoelastic properties of tendon. Understanding the interactions between tenocytes and their extracellular matrix may lead to further insight into the role tendon cells play in maintaining tendon heath and homeostasis. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:573–579, 2017. Abstract : Following loss of collagen tension, tenocytes in lax tendons immediately initiate a contraction response that significantly decreases crimp length which correlates ( R 2  = 0.6306) with a decrease in tendon length. However, as contracting tendons become taut, collagen crimp lengths were shown to return to their original patterns ( p  = 0.412). The results of this study demonstrate that the tendon crimp pattern appears to be under cellular control and is a reflection of the local mechanobiological environment of the extracellular matrix.